The impacts of flash flood towards the resident of Taman Kenari Jaya / Nur Irdina Sari Abdul Aziz and Mohd Khairul Amri Ramly - Abdul Aziz, Nur Irdina Sari; Ramly, Mohd Khairul Amri (2023)
Managing and controlling excess water after heavy rainfall or flash flood events requires an efficient drainage system. Flash floods may pose substantial threats and effects on society, the environment, and the economy to the citizens of the residential area. Within the context of flash flood impacts, the efficacy of the drainage system is crucial in lowering flood severity. Good awareness from the public and maintained drainage system can assist reduce flood risks, property loss, and environmental harm. The purpose of this research is to determine the level of awareness among Taman Kenari Jaya inhabitants on the effects of flash floods. This study will evaluate the community's view of flood hazards and the need for enhanced drainage management by identifying the rank of flash flood consequences on society, environment, and economy. Through the quantitative method approach, spreading of questionnaire with locals to examine their knowledge and opinions of flash flood impacts. The study intends to shed light on the urgent need for enhanced drainage management and flood protection techniques by studying locals' resident awareness and understanding of the impacts. Ultimately, the study aims to improve the community's resilience to flash floods and to provide a safer and more sustainable living environment.